The use of international tax planning in subsidiaries from the financial and ict sectors in the Czech Republic - Jedlička, Vít (Technická univerzita v Liberci, 2021)
Tax avoidance is an important element of management in the global economy. Managers use tax havens for reducing a company's effective tax rate. The most common practices in international tax planning can be divided into three groups: loans and their related interest, royalties, and transfer pricing. The aim of this article is to find the determinants of the tax burden faced by foreign-owned subsidiaries. Therefore, a model was created for the tax burden, focusing on the special position of subsidiaries within international tax planning. For this purpose, taxes/outcomes was established as a new dependent variable. The panel data used include Czech companies that are owned by parent companies located in other EU countries. The model distinguishes EU tax havens from regular member states; sector dummy variables are also included. The regression model that was created did not confirm the assumed dependencies. Rather, it indicated other important determinants: profitability, the share of intangible assets, size, and the dummy variable for the ICT sector. Based on the regression results, the independent variables connected with known tax planning schemes have relatively low importance. The significance of these results can be seen in the subsequent conclusions. First of all, there is no difference between the subsidiaries' tax burdens based on the parent company's location. Corporations use international tax planning whether or not they are owned from a tax haven. The second significant conclusion indicates the importance of certain sectors and their attributes concerning the tax burden. Companies from the ICT sector are linked to a lower tax burden. On the other hand, the dependencies within the financial sector are not statistically significant. From the perspective of further research, it would be constructive to incorporate the subsidiary's position within the group.
Využití mezinárodního daňového plánování v dceřiných společnostech z finančního a ICT sektoru v České republice
Keywords: tax planning; tax burden; tax havens; panel data; regression; daňové plánování; daňové zatížení; panelová data; regrese